P101 Cutting the time to treatment of chlamydia trachomatis (CT) and neisseria gonorrhoeae (NG) with near-patient molecular diagnostics: the utility of the cepheid genexpert system. (8th June 2017) - Mandlik, Emily; Plaha, Komal; Jones, Rachael; Rayment, Michael
Abstract : Introduction: The Cepheid GeneXpert® provides near-patient molecular detection of CT/NG, with results available in 90 minutes. Previous studies have illustrated the benefits to asymptomatic individuals and their partners in reducing time to treatment. Methods: A case-control study was undertaken to investigate the impact of introducing GeneXpert to a Level 3 symptomatic service. 100 patients diagnosed with CT+/-NG before and after introduction were identified. Time from attendance to treatment was measured. Using self-report over the previous three months and assuming that rate of new sexual partners remained the same and spaced equally in time, we modelled the number of partners spared exposure due to earlier treatment of CT/NG. Results: Characteristics of the study populations, and of the time to treatment and partners spared analyses are shown in the table: The time from testing to treatment was reduced by 6.2 days. The number of partners exposed/100 index patients was 19.9 pre-GeneXpert and 9.12 post-GeneXpert. Discussion: Use of GeneXpert reduced time to treatment by 66%, and 54% fewer partners were exposed to CT/NG. This study supports the personal and public health benefits of innovative, near-patient molecular diagnostics coupled with effective recall mechanisms.